Law enforcement activities of subjects of crime prevention - Polikarpova, Irina Vladimirovna; Zaitseva, Olesya Viktorovna (Вопросы безопасности, 2022)
The article is devoted to theoretical and applied research of law enforcement activities of subjects of crime prevention. The subject of scientific knowledge are the norms of criminological legislation and subordinate normative legal acts; the practice of implementing these norms by relevant subjects, as well as scientific approaches to theoretical understanding of law enforcement, factors and indicators that allow improving efficiency in the field under consideration. The aim of the work is a comprehensive empirical study of the effectiveness of law enforcement in the field of preventive criminological activity and the development of a specific mechanism for its optimization. The methodological basis of the study was made up of general scientific methods of cognition (logical, system-structural, generalization, analysis, synthesis) and a number of private scientific methods, namely statistical, sociological, nomotetic, based on the author's methodology for calculating qualitative and quantitative indicators of the state of crime and law enforcement activities implemented in the field of crime prevention. The novelty of the work lies in the fact that on the basis of the conducted research, new empirical data were obtained regarding the effectiveness of law enforcement activities of prevention subjects. The results obtained made it possible to identify the reasons for the low productivity of this activity, which should include not only certain contradictions and shortcomings of preventive legislation, but also existing defects in legal implementation techniques, distortions towards formal law enforcement and repressive practices. The main forms and methods of work of subjects of criminological prevention, the level of interaction between various bodies and subjects of crime prevention are analyzed, which made it possible to identify gaps and shortcomings of legal regulation of this activity and to form the main directions for its improvement. The scope of application of the results obtained is the practical activity of the subjects of crime prevention, as well as the conclusions and suggestions obtained can be useful for further improvement of the norms of preventive legislation.